2018
DOI: 10.1016/j.ydbio.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Transient transcriptional silencing alters the cell cycle to promote germline stem cell differentiation in Drosophila

Abstract: Transcriptional silencing is a conserved process used by embryonic germ cells to repress somatic fate and maintain totipotency and immortality. In Drosophila, this transcriptional silencing is mediated by polar granule component (pgc). Here, we show that in the adult ovary, pgc is required for timely germline stem cell (GSC) differentiation. Pgc is expressed transiently in the immediate GSC daughter (pre-cystoblast), where it mediates a pulse of transcriptional silencing. This transcriptional silencing mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…Genes up-regulated in GSCs are associated with gonad development, chromatin organisation and transcriptional regulation. This is consistent with germline differentiation being accompanied by a reduction in transcriptional activity and altered chromatin organisation (Flora et al, 2018;Zhang et al, 2014). Genes upregulated in CBs include those encoding factors involved in cellular metabolism, growth and protein production.…”
Section: Discussionsupporting
confidence: 72%
“…Genes up-regulated in GSCs are associated with gonad development, chromatin organisation and transcriptional regulation. This is consistent with germline differentiation being accompanied by a reduction in transcriptional activity and altered chromatin organisation (Flora et al, 2018;Zhang et al, 2014). Genes upregulated in CBs include those encoding factors involved in cellular metabolism, growth and protein production.…”
Section: Discussionsupporting
confidence: 72%
“…Membrane cleavage at abscission requires the Endosomal Sorting Complex Required for Transport-III (ESCRT-III) complex and the scaffold protein ALIX, and is negatively regulated by Aurora B (Eikenes et al, 2015;Matias et al, 2015). Following abscission, a brief pulse of transcriptional silencing in the presumptive cystoblast prior to Bam expression is induced by the transcriptional repressor Polar granule component (Flora et al, 2018). This allows for the accumulation of CycB, promoting cell cycle resumption and differentiation in the cystoblast.…”
Section: Mitotic Divisions In Gscsmentioning
confidence: 99%
“…All strains were grown at 25°C, except RNAi crosses, which were grown at 29°C. pgcGFP and pgc Δ used in this study have been previously reported (Martinho et al 2004;Flora et al 2018).…”
Section: Fly Stocksmentioning
confidence: 99%
“…The P-P-P (pgc promoter-pgc 5'UTR-eGFP-pgc 3'UTR) construct was generated by cloning eGFP coding sequence into a plasmid with the pgc 5'UTR and pgc 3'UTR as previously described (Flora et al 2018). The P-P-T (pgc promoter-pgc 5'UTR-eGFPtubulin 3'UTR) and P-P-K (pgc promoter-pgc 5'UTR-eGFP-K10 3'UTR) constructs were assembled by PCR amplifying a XhoI-KpnI fragment containing the α-tubulin 3'UTR (T) or K10 3'UTR (K) was then cloned into the XhoI-KpnI site of the P-P-P plasmid, respectively.…”
Section: Transgenic Linesmentioning
confidence: 99%
See 1 more Smart Citation